An exertional heat illness triage tool for a jungle training environment. Issue 4 (6th September 2017) - Smith, Mike; Withnall, R; Boulter, M
Abstract : This article introduces a practical triage tool designed to assist commanders, jungle training instructors (JTIs) and medical personnel to identify Defence Personnel (DP) with suspected exertional heat illness (EHI). The challenges of managing suspected EHI in a jungle training environment and the potential advantages to stratifying the urgency of evacuation are discussed. This tool has been designed to be an adjunct to the existing MOD mandated heat illness recognition and first aid training.